2017
DOI: 10.1111/jre.12463
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis lipopolysaccharide regulates ephrin/Eph signalling in human periodontal ligament fibroblasts

Abstract: ObjectiveEphrinA2‐EphA2 and ephrinB2‐EphB4 critically engage in bidirectional signalling to modulate alveolar bone remodelling. The present study aimed to investigate the effects of lipopolysaccharides (LPS) derived from Porphyromonas gingivalis on ephrin/Eph signalling in periodontal ligament fibroblasts (PDLFs).Material and MethodsThe primary cultured PDLFs were incubated in the absence (as a control) or presence of P. gingivalis LPS at 0.001‐10 μg/mL for 24 hours. The PDLFs were then stimulated with P. ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Our data showed that the RANKL/OPG ratio was higher under co-stimulation by CF and LPS than under mechanical stimulation alone, consistent with the results of other studies (Nokhbehsaim et al, 2010;Romer et al, 2013;Yamamoto et al, 2011). In our earlier research (Li et al, 2017), we observed upregulated ephrinA2 and downregulated EphB4 expression in PDLCs treated with LPS, suggestive of the inflammation-related dysfunction of bone remodeling via ephrinA2 and EphB4 signaling.…”
Section: Effects Of Ephrina2 Knockdown On Pdlcs Under Simultaneous Lp...supporting
confidence: 92%
“…Our data showed that the RANKL/OPG ratio was higher under co-stimulation by CF and LPS than under mechanical stimulation alone, consistent with the results of other studies (Nokhbehsaim et al, 2010;Romer et al, 2013;Yamamoto et al, 2011). In our earlier research (Li et al, 2017), we observed upregulated ephrinA2 and downregulated EphB4 expression in PDLCs treated with LPS, suggestive of the inflammation-related dysfunction of bone remodeling via ephrinA2 and EphB4 signaling.…”
Section: Effects Of Ephrina2 Knockdown On Pdlcs Under Simultaneous Lp...supporting
confidence: 92%
“…Even though, Li et al studied the effect of P. gingivalis - LPS on Eph/Ephrin signals and found that the inhibition of EphB4 expression had no significant impact on EphrinB2 in periodontal ligament fibroblasts . Zhao et al proposed that in bone metabolism, the EphB4 receptor on osteoblasts activated the EphrinB2 ligand on osteoclasts to inhibit osteoclasts, while EphrinB2 activated the EphB4 receptor to promote osteogenesis, which played a significant role in the bidirectional signaling .…”
Section: Discussionmentioning
confidence: 99%
“…31 Even though, Li et al studied the effect of P. gingivalis-LPS on Eph/Ephrin signals and found that the inhibition of EphB4 expression had no significant impact on EphrinB2 in periodontal ligament fibroblasts. 32 Zhao et al…”
Section: ■ Discussionmentioning
confidence: 99%
“…Low concentrations of LPS promote the proliferation of HPDLF. One direct approach may be that LPS promotes intracellular gene expression in cells by activating signaling pathways, such as ephrin/Eph [ 41 ], or that LPS affects Ca 2+ the transmembrane transport inside and outside cells [ 42 ]; another indirect approach is that LPS promotes cell proliferation by stimulating the production of bioactive factors in cells. However, with increased LPS intervention times, cell tolerance decreases, cells overmature, production capacity decreases, and the secretion of multiple enzymes, such as matrix metalloproteinases, increases, leading to cytotoxicity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%